Tanshinone Capsules Combined With Prednisone for Facial Seborrheic Dermatitis: A Systematic Review and Meta-Analysis of Randomized Clinical Trials - Fu, Qiang; Huang, Mengya; Tang, Lei; Zheng, Qi; Huang, Fujun; Zhou, Xun; Wang, Shumei (Frontiers in Medicine, 2022)
Background：Facial seborrheic dermatitis (FSD), also called facial seborrheic eczema, is a common disease in worldwide. Tanshinone is the mainly bioactive component extracted from traditional Chinese medicine Salvia miltiorrhiza which is widely used in treating skin inflammatory diseases. It is necessary to evaluate the clinical evidence for tanshinone treatment of FSD.This study aimed to evaluate the safety and effectiveness of tanshinone combined with prednisone in the treatment of facial seborrheic dermatitis, and to provide evidence-based evidence for clinical practice. Methods: Studies were searched from PubMed, Cochrane Library, Chinese Biomedical Literatures Database, China National Knowledge Infrastructure, Chinese Scientific Journal Database, and WanFang Database prior to October 2021, and randomized controlled clinical trials (RCT) of tanshinone combined with prednisone on facial seborrheic dermatitis. Meta-analysis was conducted according to the guidelines of the Cochrane Collaboration. Two reviewers were respectively regulate research selection, data extraction, and risk of bias assessment, a third reviewer will be settled to consulting, if necessary. Review Manager Software 5.3 will be implemented for this study. Results: A total of 10 RCTs with 916 participants were included. Nine studies reported total effectiveness, five studies reported symptom score, seven studies reported adverse events, and four studies reported recurrence rate. The duration of treatment was 4 to 8 weeks. Combination therapy showed better clinical effect compared to the prednisone(OR: 5.82; 95%CI: 3.53,9.59; p<0.00001). Combination therapy could repair skin lesions (MD: -0.40; 95%CI: -0.51,-0.30; p<0.00001), reduce skin erythema (MD: -0.58,95%; CI: -0.67,-0.49; p<0.00001), relieve skin itch (MD: -0.70; 95%CI -0.77,-0.63; p<0.00001) and desquamation score (MD: -0.64; 95%CI: -0.71,-0.56; p<0.00001). Furthermore，combination therapy could reduce adverse events (OR: 0.46; 95%CI: 0.26,0.84; p=0.01) and control recurrence rate (OR: 0.22; 95%CI: 0.13,0.36; p<0.00001). Conclusions: Compared with prednisone, tanshinone combined with prednisone may be effective in the treatment of facial seborrheic dermatitis. However, due to the high risk and ambiguity of bias in the included trials, the conclusion of this study must be interpreted carefully.